On the first geometric-arithmetic index of product graphs - Fath-Tabar G.H.,; Hossein-Zadeh S.,; Hamzeh A., (Utilitas Mathematica, 2011)
The first geometric-arithmetic index of a graph G is defined as GA 1(G) = Σe=uve⋯E(G)√d(u)d(v)/d(u)+d(v) where d(u) and d(v) are the degrees of vertices u and v, respectively. In this paper we derive upper and lower bounds on the values of GA1 index for several classes of composite graphs that arise via graph products.